Hydrodynamic Model of the Cardiovascular System - Sunnatova Dilfuza Abatovna; Tursunova Zuxra Botirovna; Ismatova Moxiraxon Abror qizi (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
The cardiovascular system plays a critical role in maintaining physiological homeostasis by ensuring effective blood circulation throughout the body. This paper presents a hydrodynamic model that integrates the principles of fluid mechanics and vessel wall elasticity to simulate pulsatile blood flow within compliant arteries. The model employs one-dimensional flow equations derived from the Navier-Stokes framework and incorporates realistic boundary conditions to mimic cardiac and peripheral vascular dynamics. Validation against clinical measurements demonstrates the model’s accuracy in replicating physiological pressure and flow waveforms. Sensitivity analysis highlights the model's capacity to capture hemodynamic changes associated with vascular stiffness, making it a valuable tool for studying cardiovascular health and disease. This integrative approach offers significant potential for advancing diagnostic methods and therapeutic strategies in cardiovascular medicine.